The Old Motel Mystery - Gertrude Chandler Warner 1890-1979; Charles Tang (USA Albert Whitman & Company, 1992)
Someone is trying to put Aunt Jane's motel out of business, but the Alden children aren't going to let that happen.
Keywords: Literature (3GdCOHs; Boxcar children (Fictitious characters) -- Juvenile fiction; General; Orphans -- Juvenile fiction; Families -- Juvenile fiction; Brothers and sisters -- Fiction; Orphans -- Fiction; Hotels, motels, etc. -- Fiction; Mystery and detective stories